2017
DOI: 10.3847/2041-8213/aa77f3
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of Gas-rich Galaxies in z ∼ 1.6 Galaxy Clusters: Evidence for Higher Gas Fractions in High-density Environments

Abstract: We present ALMA CO (2-1) detections in 11 gas-rich cluster galaxies at z∼1.6, constituting the largest sample of molecular gas measurements in z>1.5 clusters to date. The observations span three galaxy clusters, derived from the Spitzer Adaptation of the Red-sequence Cluster Survey. We augment the >5σ detections of the CO (2-1) fluxes with multi-band photometry, yielding stellar masses and infrared-derived star formation rates, to place some of the first constraints on molecular gas properties in z∼1.6 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
135
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(154 citation statements)
references
References 63 publications
17
135
2
Order By: Relevance
“…The rest of galaxies (including all those with M ⋆ > 10 11 M ⊙ ) are in agreement with the field relations. In line with these results, Noble et al (2017) found depletion timescales systematically higher than the scaling relation for nine CO(3 − 2)-detected galaxies in a cluster at z ∼ 1.6, although most are within a one standard deviation of the relation (plus several non-detection whose upper limits are in agreement with the field). Similarly, Hayashi et al (2018) presented CO(3 − 2) observations in several cluster galaxies at z ∼ 1.5 finding again systematically longer depletion timescales, although ∼ 50% of their sample might be in agreement the expected relation for the field (when non-detections are taken into account).…”
Section: The Star Formation Efficiencysupporting
confidence: 77%
See 1 more Smart Citation
“…The rest of galaxies (including all those with M ⋆ > 10 11 M ⊙ ) are in agreement with the field relations. In line with these results, Noble et al (2017) found depletion timescales systematically higher than the scaling relation for nine CO(3 − 2)-detected galaxies in a cluster at z ∼ 1.6, although most are within a one standard deviation of the relation (plus several non-detection whose upper limits are in agreement with the field). Similarly, Hayashi et al (2018) presented CO(3 − 2) observations in several cluster galaxies at z ∼ 1.5 finding again systematically longer depletion timescales, although ∼ 50% of their sample might be in agreement the expected relation for the field (when non-detections are taken into account).…”
Section: The Star Formation Efficiencysupporting
confidence: 77%
“…A thorough characterization of the star formation activity requires a census of the molecular gas mass, the main ingredient from which stars are formed. While some pioneering studies on the gas content of (proto-)cluster structures at z 1.5 have been carried out, they have focused on extreme, rare sources like Dusty Star-Forming Galaxies (DSFGs) or Active Galactic Nucleus hosts (AGN), or on samples of a few targets (Aravena et al 2012;Casasola et al 2013;Dannerbauer et al 2017;Noble et al 2017;Rudnick et al 2017;Stach et al 2017;Wang et al 2018). Despite these significant efforts, the physical properties of less extreme star-forming galaxies and the impact of the environment on their formation and evolution are still far from understood.…”
Section: Introductionmentioning
confidence: 99%
“…A question arises about what mechanisms may be responsible for this enhancement. Several physical mechanisms might contribute to a larger cross section of Mg ii in group galaxies, including higher gas fractions for satellite galaxies in dense environments (Noble et al 2017) or stronger outflows from stellar winds due to enhanced star-formation (McGee et al 2014). There seems however to be no clear consensus on the relevance of these mechanisms in groups at z ≈ 1 (Wetzel et al 2012;Rudnick et al 2017;Fossati et al 2017).…”
Section: The Origin Of Enhanced Cold Gas In Galaxy Groupsmentioning
confidence: 99%
“…Gas-rich galaxies have been observed in high-z clusters and protoclusters (Hayashi et al 2017;Noble et al 2017), with star formation rates up to 800 M yr −1 (Santos et al 2015). A large reservoir of diffuse cold and metal-rich molecular gas (M H 2 ∼ 10 11 M ) extending for 50-70 kpc was found around the radio galaxy at the center of the z=2.2 Spiderweb protocluster (Emonts et al 2018).…”
Section: Introductionmentioning
confidence: 99%